(untitled) (Raparin Journal of Humanities (RJH), 2020)
The aim of this study that to expose the level of dependency of the lecturers of Salahuddin University on the new media, generally, in education process and determine their use of these tools and determinie the arithmetical average of these uses. For this purpose, specific criteria have been set for measuring the level of dependency , after identifying the Face validity and consistency of the measurement content, the researchers distributed randomly (50) questionnaires to the lectures who were (33) males and 17 females. the results showed that the lectures depend on new media on medium, that lectures depend on new media for e-mail and the Internet to conduct their research as the ferst recuer, in contrast lectures less depend on new media for getting information about the goods they want to buy or to choose the fashion and type of clothing.